Implementasi Peraturan Bupati Nomor 41 Tahun 2016 tentang Pengelolaan Gerai dan Peberdayaan Industri Kecil dan Menengah di Kabupaten Tangerang - Ayati, Yeyet Jahrotul; Cadith, Juliannes (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2024)
This study is about the Implementation of Regent Regulation Number 41 of 2016 Concerning Outlet Management and Empowerment of Small and Medium Industries in Tangerang Regency. The problems in this study include, the still minimal involvement of the small and medium industry business sector in supporting the implementation of policies, Socialization related to the existence and implementation of outlet management and empowerment of small and medium industries is still not optimal, promotion of small and medium industry products has not been carried out optimally, and cooperation has not been established with travel and travel agencies. The purpose of this study was to determine how the implementation of Regent Regulation Number 41 of 2016 on outlet management and empowerment of small and medium industries in Tangerang Regency. The research method is qualitative. The theory used is the implementation of public policy according to Van Metter and Van Horn. The results of this study are that the implementation of Regent Regulation Number 41 of 2016 concerning Outlet Management and Empowerment of Small and Medium Industries in Tangerang Regency is not optimal.